Alternative Exercise Technologies to Fight against Sarcopenia at Old Age: A Series of Studies and Review - Wolfgang Kemmler; Simon von Stengel (Journal of Aging Research)
The most effective physiologic mean to prevent sarcopenia and related muscle malfunction is a physically active lifestyle, or even better, physical exercise. However, due to time constraints, lack of motivation, or physical limitations, a large number of elderly subjects are either unwilling or unable to perform conventional workouts. In this context, two new exercise technologies, whole-body vibration (WBV) and whole-body electromyostimulation (WB-EMS), may exhibit a save, autonomous, and efficient alternative to increase or maintain muscle mass and function. Regarding WB-EMS, the few recent studies indeed demonstrated highly relevant effects of this technology on muscle mass, strength, and power parameters at least in the elderly, with equal or even higher effects compared with conventional resistance exercise. On the contrary, although the majority of studies with elderly subjects confirmed the positive effect of WBV on strength and power parameters, a corresponding relevant effect on muscle mass was not reported. However, well-designed studies with adequate statistical power should focus more intensely on this issue.